Chronic Mania: Psychosocial impact to the family and role of community mental health team in providing care - Siti Rohana, Abdul Hadi; Suriati, Mohamed Saini; Aida Harlina, Abdul Razak; Marhani, Midin (ASEAN Journal of Psychiatry, 2014)
This case report highlights the psychosocial complications of chronic mania in a mother and the role of CMHT in improving the condition’s outcome.